The Molecular Biology of Vestibular Schwannomas and Its Association with Hearing Loss: A Review. (20th February 2012) - Celis-Aguilar, Erika; Lassaletta, Luis; Torres-Martín, Miguel; Rodrigues, F. Yuri; Nistal, Manuel; Castresana, Javier S.; Gavilan, Javier; Rey, Juan A.
Abstract : Hearing loss is the most common symptom in patients with vestibular schwannoma (VS). In the past, compressive mechanisms caused by the tumoral mass and its growth have been regarded as the most likely causes of the hearing loss associated with VS. Interestingly, new evidence proposes molecular mechanisms as an explanation for such hearing loss. Among the molecular mechanisms proposed are methylation of TP73, negative expression of cyclin D1, expression of B7-H1, increased expression of the platelet-derived growth factor A, underexpression of PEX5L, RAD54B, and PSMAL, and overexpression of CEA. Many molecular mechanisms are involved in vestibular schwannoma development; we review some of these mechanisms with special emphasis on hearing loss associated with vestibular schwannoma.